Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376658
|View full text |Cite
|
Sign up to set email alerts
|

The Social Network: How People with Visual Impairment use Mobile Phones in Kibera, Kenya

Abstract: Living in an informal settlement with a visual impairment can be very challenging resulting in social exclusion. Mobile phones have been shown to be hugely beneficial to people with sight loss in formal and high-income settings. However, little is known about whether these results hold true for people with visual impairment (VIPs) in informal settlements. We present the findings of a case study of mobile technology use by VIPs in Kibera, an informal settlement in Nairobi. We used contextual interviews, ethnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 69 publications
10
29
0
Order By: Relevance
“…In several cases participants chose to use basic or feature phones due to their specific needs as well as affordability. This is in line with results reported by [14] which showed that people with visual impairment who lived in a Kenyan informal settlement felt more independent using basic and feature phones compared to smartphones due to low levels of digital literacies and the difficulty encountered interacting with touch screen interfaces.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In several cases participants chose to use basic or feature phones due to their specific needs as well as affordability. This is in line with results reported by [14] which showed that people with visual impairment who lived in a Kenyan informal settlement felt more independent using basic and feature phones compared to smartphones due to low levels of digital literacies and the difficulty encountered interacting with touch screen interfaces.…”
Section: Discussionsupporting
confidence: 91%
“…This benefit was particularly clear for both basic mobile phones. These results are in keeping with the recent Kenyan study by [14].…”
Section: Financial Securitysupporting
confidence: 92%
See 1 more Smart Citation
“…Within the context of the research users were happy to be advised by clinicians and technicians that they trusted, but their aspiration was to increase their own knowledge so that they could make better decision for themselves. This is in line with the observation of mobile technology use of visually impaired people in Kenyan informal settlements described by Barbareschi et al [7], where participants reported being happy to be supported in their interactions with technologies but they were not always comfortable having to fully trust others.…”
Section: Discussionsupporting
confidence: 88%
“…While studies focusing on AT in terms of new technology [ 7 ]; health systems [ 8 ] and partnerships [ 9 ]; access to education and livelihoods [ 8 , 10 ]; and COVID-19 [ 11 , 12 ] are increasing, there remains very little evidence concerning the impact of AT on access to participation in activities of citizenship, and even less concerned with the very poorest persons with disabilities in the Global South. There are of course some notable exceptions, such as this informal country capacity assessment undertaken for AT provision and supply [ 13 ] and this example of the social network mediating assistive technology use in informal settlements [ 7 ]. Though much previous research has highlighted the importance of persons with disabilities being able to participate in the issues that affect their lives themselves [ 14 , 15 , 16 , 17 , 18 , 19 ], this work rarely considers the role of AT.…”
Section: Introductionmentioning
confidence: 99%